Association Between Serum Uric Acid Levels/Hyperuricemia and Hypertension Among 85, 286 Japanese Workers. Issue 1 (25th July 2015) - Yokokawa, Hirohide; Fukuda, Hiroshi; Suzuki, Akihito; Fujibayashi, Kazutoshi; Naito, Toshio; Uehara, Yuki; Nakayama, Akiyoshi; Matsuo, Hirotaka; Sanada, Hironobu; Jose, Pedro A.; Miwa, Yuichi; Hisaoka, Teruhiko; et al.
Abstract : This cross‐sectional study from January 2012 to December 2012 aimed to examine the sex‐specific association between serum uric acid (SUA) levels/hyperuricemia and hypertension among Japanese patients. SUA level, medical histories, and lifestyle‐related items were collected from 85, 286 of 136, 770 participants. Among those with hyperuricemia, the median age was 46 years and 97% were men, which was significantly different than those without hyperurecemia (44 years and 56%, respectively; P <.01). Hyperuricemia was 1.79 times more likely in hypertensive men than normotensive men and almost six times more likely in hypertensive women (odds ratio=5.92 and adjusted odds ratio=1.33 for men and adjusted odds ratio=1.81 for women) after multivariate analysis. SUA quartiles positively correlated with systolic and diastolic blood pressures in both sexes. Hyperuricemia and SUA levels were significantly associated with hypertension in both sexes. These findings underscore the importance of maintaining normal SUA levels to manage and prevent hypertension. Better management of SUA as well as blood pressure may have potential in preventing future cardiovascular disorders.